SEROPREVALENCE OF MEASLES IgG ANTIBODIES IN CHILDREN OF SCHOOL GOING AGE - Ferdoos, Saiba; Khan, Shakir; Azeem, Zahid; Naveed, Abdul Khaliq; Ali, Ghazanfar; Malik, Nazia; Zaidi, Syed Sohail Zahoor (Pakistan Journal of Physiology, 2018)
Background: Measles is highly contagious infectious disease and considered to be leading cause of death among young children. Although vaccination process of measles is well ascertained but still its associated morbidity and mortality is high among children of developing countries. This study was designed to see the level of measles IgG in children in District Bagh of Azad Jammu & Kashmir. Methods: Measles IgG antibodies were screened in total of 250 school going children (4–8 years) in the District Bagh, Azad Jammu and Kashmir were enrolled. The subjects were grouped on age basis; Group A had children of 4–5 years, Group B comprised of children of 5–6 years, Group C contained children of 6–7 years and Group D had age 7–8 years. A The collected samples were transferred to the Molecular Virology Laboratories at National Institute of Health (NIH), Islamabad for detection of measles IgG antibodies. Measles antibodies were estimated by using kits for Enzyme Linked Immunosorbant Assay. Results: There were 10 (4%) children in Group A, 18 (7.2%) were in Group B, 42 (16.8%) were in Group C, and 180 (72%) children were in Group D. Out of 250 children 61 (24.4%) were detected as unprotected and 13 (5.2%) were at borderline and 176 (70.4%) had protective antibody level against the measles virus. Conclusion: Significant number of children is under potential risk to develop measles infection. No significant relation could be established between disease, age, and gender. Pak J Physiol 2018;14(1):13–5